Lussazione gleno-omerale: eziopatogenesi, anatomia patologica, classificazioni - Carbone, S.; De Cupis, M. (Lo Scalpello - Journal, 2018)
GLENOHUMERAL INSTABILITY: AETIOPATHOGENESIS, PATHOLOGIC ANATOMY, CLASSIFICATIONSThe shoulder is the most frequently dislocated joint in the body owing to its large range of motion and small area ofarticulation between the humeral and the glenoid surfaces. Traumatic shoulder dislocations, especially thoseassociated with injury to the labroligamentous or bony stabilizers of the joint, lead to further reduction of articularsurface contact with resultant glenohumeral instability and recurrent shoulder dislocations. Classification ofinstability mechanism and direction is important for the choice of the right treatment.